2011
DOI: 10.2106/jbjs.j.01292
|View full text |Cite
|
Sign up to set email alerts
|

Revision Surgery Following Operations for Lumbar Stenosis

Abstract: The likelihood of repeat surgery for spinal stenosis declined with increasing age and comorbidity, perhaps because of concern for greater risks. The strongest clinical predictor of repeat surgery was a lumbar spine operation prior to the index operation. Arthrodeses were not significantly associated with lower rates of repeat surgery after the first postoperative year, and patients who had had complex arthrodeses had the highest rate of reoperations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 20 publications
5
97
1
4
Order By: Relevance
“…The rate of additional surgery for ASD following double-level PLIF was reportedly 5-10 % [20,21], which is lower than that following repeat PLIF for ASD (11 %) in the present study. Deyo et al [22] reported in their study of 31,543 patients with surgery for lumbar stenosis that previous spinal surgery was the strongest risk factor for repeat surgery and that the hazard ratio for this was 1.58. These results suggest that patients undergoing repeat PLIF for ASD would incur more risk factors for additional surgery than those undergoing single-or doublelevel PLIF as the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of additional surgery for ASD following double-level PLIF was reportedly 5-10 % [20,21], which is lower than that following repeat PLIF for ASD (11 %) in the present study. Deyo et al [22] reported in their study of 31,543 patients with surgery for lumbar stenosis that previous spinal surgery was the strongest risk factor for repeat surgery and that the hazard ratio for this was 1.58. These results suggest that patients undergoing repeat PLIF for ASD would incur more risk factors for additional surgery than those undergoing single-or doublelevel PLIF as the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is the possibility that fusion of one or two levels in a degenerated lumbar spine will create adjacent problems due to altered biomechanics and increased loads on the unfused segments (Park et al 2004;Mannion et al 2014b) We did not study the reoperation rate related to treatment and pain predominance. Recent studies have however shown that fusion is not associated with significantly lower rates of repeat surgery after the first postoperative year (Deyo et al 2011). Complex fusions were associated with the highest rates of reoperations (Deyo et al 2011).…”
Section: The Role Of Spinal Fusion In Dsmentioning
confidence: 90%
“…Recent studies have however shown that fusion is not associated with significantly lower rates of repeat surgery after the first postoperative year (Deyo et al 2011). Complex fusions were associated with the highest rates of reoperations (Deyo et al 2011).…”
Section: The Role Of Spinal Fusion In Dsmentioning
confidence: 90%
“…Complications from surgery are common and may result in repeat surgery, with reoperation rates being as high 8 % within two years from index procedure [35] and 23 % within 10 years [53]. Repeat surgery is also associated with lower effectiveness and greater complications as compared with initial surgery [54]. Furthermore, the older population may be at higher risks of developing major medical complications from surgical procedures including acute myocardial infarction, pulmonary embolism and stroke, along with poor wound healing, infection and mortality [55], hence the risks and benefits must be [55].…”
Section: Discussionmentioning
confidence: 99%